Granny made me an anarchist : General Franco, the Angry brigade and me - Christie, Stuart, 1946-2020 (London : Scribner, 2004)
Stuart Christie was at the centre of two events that define a lost radical period of British history - a period when a large section of the people thought they could change the world. In 1964, Christie was arrested in Spain and charged with attempting to assassinate General Franco. The penalty was death by garroting. He was eighteen, far from his home in Glasgow, and could speak no Spanish. The worst part was that the charge was true. Christie was convicted, escaped the death sentence and became Britain's most famous anarchist. In 1971 he was arrested again, this time in Britain, suspected of being a member of The Angry Brigade. The Angry Brigade was an anarchist group that had - while ensuring that no one would be injured - blown up several London embassies and the houses of prominent figures in the British establishment. Their trial became a sensational confrontation between the state and those who tried to overthrow it. Christie was acquitted. Four others were sent to gaol. Stuart Christie's story encompasses these two events, and the time in between - when a sizeable proportion of the people in Britain thought that the whole system of our society could be changed for the better, if only the right spark could be struck. It wasn't. People have never thought that way again
Keywords: Christie, Stuart, -- 1946-2020.; The Angry Brigade; Anarchist black cross; Anarkism -- 1900-talet -- Storbritannien; Anarkism -- 1900-talet -- Spanien